2010
DOI: 10.1016/s1473-3099(09)70334-2
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory influenza immunisation of health-care workers

Abstract: Seasonal influenza imposes an enormous but poorly defined burden of excess deaths, hospital admissions, and health-care costs, and often spreads within health-care facilities. Hospital patients with influenza are a potential source of infection for health-care workers that are not immunised, with attack rates among health-care workers of 18–24%.1 Unfortunately, health-care workers infected with influenza often continue to work, despite symptoms, with potentially devastating consequences for high-risk patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Thus, we can say that knowledge does not necessarily affects the action. Other authors (20)(21)(22)(23) have also shown that the benefits of vaccination related to patients were little considered by some professionals, and which in this study also does not appear as the main motivators for vaccination. These data can be interpreted as a limited understanding of the benefits generated by vaccination in health professionalpresent, more intensely in those who have not adhered to this practice.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Thus, we can say that knowledge does not necessarily affects the action. Other authors (20)(21)(22)(23) have also shown that the benefits of vaccination related to patients were little considered by some professionals, and which in this study also does not appear as the main motivators for vaccination. These data can be interpreted as a limited understanding of the benefits generated by vaccination in health professionalpresent, more intensely in those who have not adhered to this practice.…”
Section: Discussionmentioning
confidence: 47%
“…In another study, the authors used different intervention strategies related to accessibility, including the training of workers to act vaccinating their colleagues in the workplace, prolongingvaccination time beyond the routine, mass vaccination day,mobile vaccinators moving aroud workplece which, combined with educational measures and diverse dissemination, obtained an increase of 77.0% to 84.7% in coverage of the institution (26) . It is also important to remember that facilitating access to vaccination through measures such as increasing the number of days of the campaign, making it available within the various work shifts and leaving the option for the professional to vaccinate in the workplace or go to a fixed location with easy access are important strategies for acquiring adequate coverage (15,21,23) . Nevertheless, isolated measures in campaigns involving only education or only promotionhave little impact on increasing adherence to vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Da medizinisches Personal aufgrund seiner beruflichen Tätigkeit ein erhöhtes Expositionsrisiko gegenüber Influenzaerkrankten hat, dient die Impfung einerseits dem individuellen Schutz der Beschäftigten, andererseits können dadurch Infektionsübertragungen auf Patienten vermieden werden [12]. Allerdings lässt sich nur ungefähr jeder fünfte Beschäftige aus dem Gesundheitswesen in Deutschland gegen Influenza impfen.…”
Section: In Der Diskussion Influenza Im Deutschen Gesundheitswesenunclassified
“…Impfungen für medizinisches Personal werden meist als etwas betrachtet, das man akzeptieren oder auch ablehnen kann. Die Wahlfreiheit hängt aber auch davon ab, inwieweit die eigene Entscheidung andere Personen beeinträch-tigen kann [12]. Die ethische Pflicht, anderen nicht zu schaden, das heißt in diesem Kontext, keine Influenzainfektion zu übertragen, überwiegt nach unserem Ermessen der relativ geringen Gefahr, aufgrund der Influenzaimpfung relevante Nebenwirkungen zu erleiden [18,38,41,42,43,44,45,46,47].…”
Section: Verpflichtende Influenzaimpfungunclassified
“…There is no consensus on whether mandatory influenza immunisation policies for healthcare workers should be instituted 4549. Recently, the Society for Healthcare Epidemiology of America has endorsed a policy in which annual influenza vaccination is a condition of both initial and continued healthcare worker employment and/or professional privileges 50.…”
Section: Which Interventions Increase Uptake?mentioning
confidence: 99%